Determinants of rural practice among a cohort of dental professionals in Australia - Santosh Kumar Tadakamadla; Sudheer Babu Balla; Jyothi Tadakamadla; Libby Semmens; Sarah Down; Carol McKinstry; Jane Mills (BMC Medical Education)
Abstract Background Most research on tracking practice locations of health students has focused on medical students, particularly the factors influencing their choice to work in rural and remote areas. However, there is limited research on how rural origin and training in regional or rural settings affect the employment destinations of dental and oral health graduates. This paper explores the practice locations of dentistry and oral health therapy (OHT) graduates from rural backgrounds compared to those from metropolitan areas in Australia. Materials and methods The target population was dental and OHT graduates from La Trobe University’s Rural Health School (Australia) who completed their studies between 2009 and 2023. The graduates’ primary place of practice was sourced from the Australian Health Practitioners Regulation Agency (AHPRA) data. The 2019 Modified Monash Model (MMM) was used to categorise the students’ original place of residence by rurality and practice locations. Multivariable analyses were conducted to explore the association between home and practice locations while controlling for the effect of socio-demographic characteristics collected from students at enrolment. Results Data were available for 819 graduates matched to the AHPRA register. Of these, 541 (66.1%) were dentists, and 278 (33.9%) were OHTs. The majority were female (56.7% dentists and 81.7% OHTs), 11.3% (dentists) and 21.6% (OHTs) of the graduates originated from rural and remote areas, 16.6% (dentists) and 18% (OHTs) from regional areas, and 72.1% (dentists) and 60.4% (OHTs) from metropolitan areas. Multinomial logistic regression analyses for dentists and OHTs identified that , having a regional background, or having a rural or remote background were the most significant predictors for regional, rural/remote practice over metropolitan areas. Conclusion Regional background is the strongest predictor for graduate dentists and OHTs practicing in Australia’s regional or rural and remote locations. Similarly, students from rural and remote locations were highly likely to practice in rural/ remote locations. Increasing the recruitment of students with rural backgrounds may positively impact graduates’ decisions to practice in rural areas.